Evaluation of In-Vitro Anthelmintic Potential of Nyctanthes Arbor-Tristis Linn Leaves and Its Phytochemical Correlation - Salhaita Chandrakant; Choudhury P.K; Sharma Maya (Asian Journal of Pharmaceutical Research and Development, 2025)
The present study investigated the in-vitro anthelmintic potential of Nyctanthes arbor-tristis Linn leaves and explored its correlation with phytochemical constituents. Leaf powder was extracted using [solvent, e.g., methanol/ethanol/aqueous], and preliminary phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and phenolic compounds. The anthelmintic activity was evaluated using Pheretima posthuma as the test model, with Piperazine citrate as the standard comparator. Results demonstrated dose-dependent paralysis and mortality of worms, with higher concentrations producing effects comparable to the standard drug. The observed anthelmintic activity is likely attributable to the bioactive phytoconstituents present in the leaf extract. These findings support the traditional use of Nyctanthes arbor-tristis in treating helminthic infections and provide a basis for further studies aimed at isolating and characterizing its active compounds for potential therapeutic applications.